Edukasi Digital: Membangun Semangat Belajar Anak di SD Kristen Duta Cendikia Batam - Siregar, Viktor Deni; Sihombing, Obet Edomta; Simanjuntak, Martha Eunike; Simarmata, Lestari; Crisena, Crisena; Sinaga, Meriana; Nababan, Putri Sion; Sari S, Sarda Novita; Harianja, Ester Novalina; Ritonga, Naomi Yolanti Octavia (Jurnal Pengabdian Masyarakat Nusantara (JPMN), 2025)
A Community Service (PKM) activity with the theme "Digital Education: Building Children's Enthusiasm for Learning Amidst the Challenges of the Technological Era" was held at Duta Cendikia Christian Elementary School, Batam as an effort to increase the motivation and digital literacy of elementary school students. This program was motivated by the low enthusiasm for learning in students due to the undirected use of technology and teachers' limitations in integrating digital media into learning. The PKM activity was carried out for two months, involving teachers and students in grades IV–VI through a participatory approach, digital learning media training, and technology-based interactive activities. The results of the activity showed a significant increase in students' enthusiasm for learning, demonstrated by active involvement, creativity, and enthusiasm during the digital learning process. The majority of participants (more than 85%) expressed satisfaction with the materials, methods, and benefits of the activity, with a tangible increase in digital literacy. Interactive learning, a positive learning environment, and project-based contextual strategies have proven effective in fostering learning motivation in the digital era. Teachers also gained increased pedagogical competence in managing technology in an educational manner. Overall, this PKM activity contributes to building an adaptive, creative, and character-based learning ecosystem that not only fosters a passion for learning but also fosters responsible and Christian-based learning behaviors. This program is expected to serve as a model for good practices in implementing digital education in elementary schools to address the challenges of education in the technological era.